Updates on the ocular manifestations and treatment of SJS/TEN - Chie Sotozono; Mayumi Ueta (Allergology International)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are acute inflammatory disorders that affect the skin and mucous membranes, and in 40–84 % of SJS/TEN cases, the ocular complications that are often overlooked due to severe systemic symptoms. Specific ocular findings at the acute-phase include conjunctival hyperemia, pseudomembrane formation, and epithelial defects, and severe acute-phase ocular involvement strongly correlates with long-term visual impairment. Thus, it is vital to diagnose ocular involvement early at the acute stage and suppress inflammation on the ocular surface to protect corneal epithelial stem cells. As outlined in the official Japanese treatment guidelines for SJS/TEN cases with ocular involvement, corticosteroid pulse therapy and topical application of 0.1 % betamethasone eye-drops within four days of disease onset significantly reduces ocular sequelae. Early intervention with amniotic membrane transplantation helps reduce scarring and potential loss of vision. As for genetic-related factors, NSAIDs (nonsteroidal anti-inflammatory drugs) and cold medications are major triggers for SJS/TEN with severe ocular complications, with genetic predispositions involving TLR3 and prostaglandin E receptor 3 (subtype EP3) contributing to disease susceptibility. These genetic–environment interactions influence disease onset and progression. At chronic phase, severe dry eye and visual impairment are major long-term sequelae, and both surgical and non-surgical interventions have been applied to obtain favorable long-term treatment outcomes. In summary, early ophthalmic intervention is critical in preventing SJS/TEN-related ocular sequelae, and further research into genetic and immunological mechanisms is essential for better diagnosis and treatment.